2003
DOI: 10.1093/esr/19.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inequality. Unequal Access to Organizational Power and the Gender Wage Gap

Abstract: In this paper, it is argued that women's limited access to organizational power structures is a constituent part of the explanation of gender wage inequality. Multi-level analyses conducted on a comprehensive Swedish data set combining information on a large number of private sector employers and all their employees confirm that establishments' gender wage gaps are wider the stronger the male representation among organizational decision-makers, net of individuals' human capital and various organizational featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 40 publications
3
84
2
3
Order By: Relevance
“…The difference between the male and female headed departments showed a tendency to decrease with the higher proportion of women in the departments. Szulkin (1999 and2003), Cohen and Huffman (2007) and the study by Cardoso and Winter-Ebmer (2010) concluded that the gender wage gap reduced with a greater representation of women in management. Our fi ndings are consistent with these.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference between the male and female headed departments showed a tendency to decrease with the higher proportion of women in the departments. Szulkin (1999 and2003), Cohen and Huffman (2007) and the study by Cardoso and Winter-Ebmer (2010) concluded that the gender wage gap reduced with a greater representation of women in management. Our fi ndings are consistent with these.…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by more freedom in determining wages in the private sector where wages are not subject to wage regulations. In the study by Hultin and Szulkin (2003), the authors used a signifi cantly broader sample of employees. They used an employer-employee matched data set covering a large number of Swedish private sector fi rms.…”
Section: Gender Wage DI Erences: Results Of the Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 7.2 percent of the hires in our data are non-western migrants, only 3.7 percent of the managers come from this group. 7 A closely related literature studies managers from a gender perspective and shows a positive correlation between female management and female wages (Carrington and Troske 1995;Hultin and Szulkin 2003). Using a matched employer-employee dataset for Portugal, Carduso and Winter-Ebmer (2007) estimate the effect of withinestablishment manager changes and find that female-led firms pay a premium to female workers of almost 5 percent.…”
Section: Introductionmentioning
confidence: 99%